(untitled) (Sirte Journal of Medical Sciences, 2022)
Background: Cigarette smoking is a crucial public health problem with 1.3 billion smokers around the world, causing 5 million death annually. In Malaysia, the prevalence of cigarette smoking among both male and female Malaysian adults aged 15 years and above is 23.1%, and is highest in those aged 21-30 years old. Although majority of people in Malaysia have knowledge on harmfulness of smoking and second-hand smoke, their perception towards smoking is not clearly determined. Thus, we conducted a study to determine the perception and awareness of risk of cigarette smoking in Sibu community. Methods: A cross sectional study was conducted in Sibu districtdistrict from April to May 2018, involving 356 respondents. A questionnaire was used to collect data, which consists of four sections. These covered the sociodemographic data, smoking status of respondents, their perception towards cigarette smoking and knowledge regarding the risk of cigarette smoking and second-hand smoke. The data were then analyzed using SPSS version 22. Results: The respondents’ overall perception towards cigarette smoking is strongly positive with 50.6% out of 356 respondents. Awareness on risk of cigarette smoking is high with 81.7% having good awareness level in contrast to only 3.1% having poor awareness level. There is a significant difference on perception level between smoking status, genders, different education level and different occupation. There is also a significant difference between awareness of risk of cigarette smoking and education level and occupation. Conclusion: Generally, the perception level towards cigarette smoking among sibu community is strongly positive and thus, against smoking .As well as their awareness level towards risk of smoking is relatively high with majority having good awareness level. This shows that most of Sibu community have good knowledge of cigarette smoking and are against smoking.